Identification of Trichomonas vaginalis Parasites In Commercial Sex Workers Conducting Examinations At The Mawar Clinic PKBI Bandung, Indonesia - Kodariah, Liah; Nisa, Putri Khoerun; Pakpahan, Suyarta E.; Aulia, Syifa (Asian Journal of Health and Applied Sciences, 2022)
Trichomoniasis is a sexually transmitted infection (STI) caused by the pathogenic Trichomonas vaginalis protozoa parasite found in the female genitourinary tract and can cause vaginal discharge, in severe conditions, vaginal inflammation will occur. Trichomoniasis has a high risk of infecting groups that often have multiple partners, such as Commercial Sex Workers (CSWs). This study aims to determine the presence or absence of Trichomonas vaginalis parasites in the urine sample of Commercial Sex Workers who conduct examinations at the Mawar Clinic PKBI Bandung. The research method used is observation. The sample is the urine of a prostitute who performs an examination at the Mawar Clinic PKBI Bandung, Indonesia. The examination was carried out in two ways, namely the wet method and the Giemsa staining method, which was carried out in the Rajawali Bandung Institute of Health laboratory. The results showed that out of 30 samples, 11 urine samples of CSW were infected with Trichomonas vaginalis,. The conclusion of this study is that Trichomonas vaginalis parasites were found in urine samples of prostitutes who were examined at the Mawar Clinic PKBI Bandung.